Value-add application of waste plastic in road pavement construction - Lim, Roline Hui Xin (2019)
Plastic waste disposal has imposed a serious problem all over the world and many studies have been finding new ways to recycle these plastics. Additionally, the opening of the Jurong Rock Cavern has produced plentiful amounts of Jurong Sedimentary Rocks (JSRs) which have the potential to be used in the construction of road pavements. The aim of this study is to investigate the feasibility of using the JSRs as aggregates for low traffic Porous Asphalt Mix (PAM) pavements with the use of plastic polypropylene (PP) as additive to improve the PAM’s performances. Prior to the main experiment, performance tests were carried out on 5 different gradations of granite and the best gradation design was determined. The chosen design was used for the JSR aggregates. Hydrated lime was used as fillers for the mix design. Three blends A, B and C with 0%, 5% and 10% of PP content respectively were mixed using the wet process and fabricated following the Marshall specimen sizing. The 3 blends were tested on through laboratory tests such as the Marshall Stability test, Permeability test, Indirect Tensile Strength Test and Moisture Susceptibility Test to evaluate each of its performance. Tests such as the Cantabro Abrasion test and Draindown test were also carried out to evaluate if the 5.0% binder content used was adequate for the mix. Through the experiments, 5.0% of binder content use was found to be adequate. All 3 blends have passed the Marshall Stability for low strength pavements. Blends B and C with PP added was found to have significantly greater Resilient Modulus compared to Blend A. In terms of Moisture Susceptibility, only Blend C with 10% plastic displayed good resistance towards water while Blend B with 5% plastic did not had satisfactory results. Although Blend C with 10% plastic had lower rate of permeability than Blends A and B, it still portrayed satisfactory permeability rate. Further research is needed to further evaluate the feasibility of using JSR as road pavements with the addition of PP.